Pengaruh Metode Bermain Sambil Belajar Al-Qur’an terhadap Motivasi Belajar di Masa Transisi Covid 19 ke Tatap Muka di TQA an Namlu Karawang - Ike Aulia Ramadani Mulyono; Ajat Rukajat; Khalid Ramdhani (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This study aims to knowing the effect of play while learning on the learning motivation Al-Qur’an in covid 19 transition in TQA An Namlu Karawang by using the quantitative eksperimental method. The population in this study was all students of TQA An Namlu Karawang by taking samples of DTA 2 class which total 11 students using sampling purposive. Analysis of the study data using T-Test with Paired Sample T-Test and N-Gain Normality test and has passed the prerequisite test for the normality test. The data collecting using observation data, documentation, and test. The result showed that 1) the students’ learning motivation during covid 19 transition decreased after distance learning (PJJ). 2) the play while learning method is one of the fun method that can be applied in learning Al-Qur’an to increase students’ learning motivation. 3) the play while learning method shows that it has an effect on the Al-Qur’an learning motivation in students during the covid 19 transition period which is shown in the results of the paired sample t-test where the significance value is 0,000 (meaning <0,05) and the n-gain normality test is 0,51 (51,04%) or in the medium category. It can be stated that Ho is rejected and Ha is accepted. This means that the play while learning method has an effect on Al-Qur’an learning motivation during the covid 19 transition period in students at TQA An Namlu Karawang.